MARKETING FACTORS AFFECTING DECISION MAKING PROCESS OF ELECTRIC VEHICLES - Suttirak, Thanapon (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to study the marketing factors affecting purchase decision process the electric vehicle (EV). Using the survey research model. The sample used in this study was 400 Consumers who are interested in electric cars and live in Bangkok. Using an online questionnaire as a data collection tool. The statistics used in the data analysis were frequency, percentage, mean, standard deviation, T - test, F - test (One Way ANOVA), and enter multiple regression. The statistical significance level was set at the 0.05 level. The result of this study showed that the sample consumers gave importance to the market factor. Product acceptance factor and the overall electric vehicle (EV) purchase decision process are at a high level. The hypothesis testing revealed that 1) Consumers with different personal factors had no difference in the decision - making process for electric vehicle (EV) purchase; 2) Marketing factors were products and marketing promotions and 3) The product acceptance factor was intrinsic motivation ease of use and perceived benefits Influence consumers’ decision to purchase an electric vehicle (EV) in Bangkok. Suggestions: Entrepreneurs should focus on the durability of electric vehicles (EVs), have Quick Charge charging points at various points thoroughly, and have a variety of media channels to reach customers such as televisions, websites, Facebook, Instagram, etc. Free maintenance in the first 6 months, after-sales service of the center. Electric vehicle (EV) batteries are guaranteed for 10 years or 100,000 kilometers to give consumers peace of mind and concerns about the use of electric cars are gone.